Improvement of Self-Efficacy of Mothers Inpostpartum Period Through Home Visit by Health Workers in Aceh - Said Usman; Dewi Marianthi; Irwan Saputra; T.M. Rafsanjani (Institute of Medico-legal Publications Pvt Ltd, 2021)
World Health Organization recorded that about 44% of infant deaths in 2012 happened in the first 28 daysafter birth, and 78.5% of deaths happen in the first week after births. It was estimated that 80% of infantdeaths happen at home (with little or no contact with health workers). Good quality care service for infantsespecially newborns at home is a serious challenge, thus an effort that could be performed is to optimizethe role of health workers in the community by doing homevisit.The goal of this researchto identify theself-efficacy of postpartum mothers before home visit and after home visit, to compare the self-efficacy ofintervention group and control group on newborn care by means of health workers role during home visit.This research use quantitative research with quasi-experimental non-equivalent control group design method.The sample of the research was health workers; each with responsibility of one fostered family of a motherin postpartum period. The research site for the intervention group was the working area of UleeKarengHealth Center, and for the control group was the working area of Baiturrahman Health Center. The result ofthe research revealed that there was a change in self-efficacy of postpartum mothers on newborn care afterthree home visits by the health workers. The difference of the average efficacy score was 12.5, with p valueof 0.0001. When the efficacy of postpartum mothers from the intervention group (who received homevisits) was compared to that of mothers from the control group, there was a significant difference found,with p value of 0.003. Home visit executed by the health workers can improve self-efficacy of thepostpartum mothers on newborn care. This can be seen from the difference between self-efficacy of thepostpartum mothers before and after home visit by the health workers.